The new oral antiviral agents for COVID-19 - S.L. Seneviratne; C. Dalugama; P. Madanayake; B. Samaraweera; J. Kariyawasam; V. Abeysuriya (Sri Lanka College of Internal Medicine, 2022)
Coronavirus Disease-2019 (COVID-19), has so far affected more than 275 million individuals globally and caused over 5.3 million deaths. With an effective vaccine, disease and infection could be prevented, whereas with antivirals and monoclonal antibodies, disease progression could be mitigated. In recent months, there has been much interest in evaluating the use of oral antivirals, in those having mild disease and associated risk factors for disease progression (such as multiple comorbidities), in view of preventing severe COVID-19. Our review discusses the known properties and identified effectiveness of three oral antiviral drugs (Molnupiravir, Paxlovid and AT-527) for COVID-19 (as at end of December 2021) and explores their potential role in mitigating the ill effects of the on-going COVID-19 pandemic.